Cover Feature: Tailoring the NIR‐II Photoluminescence of Single Thiolated Au25 Nanoclusters by Selective Binding to Proteins (Chem. Eur. J. 39/2022). Issue 39 (27th June 2022) - Bertorelle, Franck; Wegner, K. David; Perić Bakulić, Martina; Fakhouri, Hussein; Comby‐Zerbino, Clothilde; Sagar, Amin; Bernadó, Pau; Resch‐Genger, Ute; Bonačić‐Koutecký, Vlasta; Le Guével, Xavier; Antoine, Rodolphe
Abstract : Nanocluster in a jewel case : A single, atomically precise gold nanocluster (Au25 ) has been incorporated inside bovine serum albumin protein. A striking increase in Au25 ‐BSA NIR‐II photoluminescence was observed as compared to Au25 . The results reveal the intricate role of protein rigidification and the involvement of different excited states in the generation of NIR‐II emissions. More information can be found in the Research Article by V. Bonačić‐Koutecký, X. Le Guével, R. Antoine, and co‐workers (DOI: 10.1002/chem.202200570 ).